Molecular oxygen induced free radical oxythiocyanation of styrenes leading to α-oxothiocyanates. Issue 23 (10th June 2015) - Liu, Kui; Li, Da-Peng; Zhou, Shao-Fang; Pan, Xiang-Qiang; Shoberu, Adedamola; Zou, Jian-Ping
Abstract: A facile and efficient protocol of oxythiocyanation of styrenes with ammonium thiocyanate has been developed. The reaction proceeded at room temperature using oxygen as sole oxidant to afford the α-oxothiocyanates via radical pathway in moderate to good yields. This method is straightforward, green and cost-effective, requires no catalyst and additives. Graphical abstract: